Structural, Electronic, and Optical Properties of HgSe Monolayer: Density Functional Theory Calculations - Ali, Aqeel M.; Mohammed, Mohanned J. (Iraqi Journal of Physics, 2025)
To investigate the structural, electrical, and optical properties of a single layer of two-dimensional mercury selenide (HgSe), density functional theory is used for the analysis of the material. To ensure the monolayer's structural and thermal stability, it is of the utmost importance to ascertain the phonon frequency. Computer simulations based on first principles were used in order to investigate the structural lattice parameter, which is in good agreement with experimental results. The two-dimensional HgSe is dynamically stable according to the positive phonon frequencies. The 2D-HgSe has the semiconductor characteristic of a direct band gap of about 1.731 eV, located at the Γ point. The static dielectric constant is 1.34 for a semiconductor characteristic. The HgSe monolayer is a transparent material with a static refractive index of 1.16, besides an anti-reflective characteristic. The refractive index had a lowest value of 0.76 at high energy. 2D-HgSe has a UV optical absorption characteristic.